A positive scapular assistance test is equally present in various shoulder disorders but more commonly found among patients with scapular dyskinesis. (November 2018) - Rabin, Alon; Chechik, Ofir; Dolkart, Oleg; Goldstein, Yariv; Maman, Eran
Abstract: Objective: Assess the frequency of a positive scapular assistance test (SAT) in different shoulder disorders and establish its association with scapular dyskinesis. Design: Cross-sectional. Setting: Shoulder clinic. Participants: Seventy-four patients. Main outcome measures: The SAT and visual assessment of scapular movement were performed by a physical therapist. An orthopaedic surgeon classified participants into 4 diagnostic categories: rotator cuff disease, superior labrum anterior posterior lesion (SLAP), shoulder instability, and other. Results: Twenty-seven (36.5%) participants presented with a positive SAT. The SAT was positive among 9 of 28 participants (32.1%) with rotator cuff disease, 7 of 23 participants (30.4%) with SLAP lesions, 9 of 21 participants (42.9%) with shoulder instability, and 2 of 2 participants (100.0%) with other pathologies. The frequency of a positive SAT did not differ between the various diagnostic categories (P = 0.64). The SAT was more frequently positive among participants with scapular dyskinesis (48.5% versus 26.8%, P = 0.05). Conclusions: The SAT is found similarly positive among patients with various common shoulder disorders. Although associated with scapular dyskinesis, the SAT was positive in less than half of those demonstrating scapular dyskinesis suggesting the SAT may help identify patients in whom altered scapular movement is contributing to shoulder pain. Highlights: The SAT is similarly positive in different shoulder disorders. The SAT is more frequently positive among patients with scapular dyskinesis. The SAT may identify patients in whom scapular dyskinesis is contributing to shoulder pain.